Shareholders Wealth Creation through Economic Value added (EVA) - Dhond, Arvind A. (SFIMAR Research Review, 2010)
Maximizing shareholders’ wealth has become the new corporate paradigm. Maximizing the shareholders’ wealth means maximizing the net worth of the company for its shareholders’. This is reflected in the market price of the shares held by them. Therefore wealth maximization means creation of maximum value for company’s shareholders’ which means maximizing the market price of the shares. Shareholders value maximization, which is the heart of economic growth, as a long-term proposition that delivers higher economic output and prosperity through productivity gains, employment growth and higher wages. Management’s most important mission is to maximize shareholders wealth. Therefore wealth creation is dependent on management’s performance. In order to measure the performance of company’s management; accountants, finance managers, investors, analysts and other users use several tools. In the past decade sea changes has been made in the performance and measurement criteria of corporate entities, from the traditional profit based measures like. Earning Per Share (EPS), Return On Capital Employed (ROCE), Return On Net Worth (RONW), Net Operational Profit After Tax (NOPAT) and Earning Before Interest and Tax (EBIT), to the new ’trendier’ value based performance measures, like Market Value Added (MVA), Shareholder Value Added (SVA), Cash Value Added (CVA), and Economic Value Added (EVA). Shareholders need some tools, which would enable them to assess and forecast the performance of company’s management. Shareholders expect to achieve the required return from their investments. In order to measure the performance of company’s management, various users use several tools. Major problem of the shareholders is to understand that among the various tools available in order to measure the performance of company’s management, which tool has more relationship with shareholders wealth creation. Among the modern tools. Economic Value Added (EVA) has received attention and recognition in accounting and financial areas as a vital tool to measure corporate performance. Economic Value Added (EVA) concept is a correct criterion in performance management, because it includes all the cost of capital employed.